Underwater terrain-aided navigation method based on improved Gaussian sum particle filtering. (31st December 2018) - Chen, Pengyun; Chang, Jianlong; Han, Yujie; Yuan, Meini
To solve the nonlinear Bayesian estimation problem in underwater terrain-aided navigation, a terrain-aided navigation method based on improved Gaussian sum particle filter is proposed. This method approximates the Bayesian function using multiple Gaussian components, and the components can be obtained by radial basis function neural network. This method has no resampling process, the particle depletion of particle filtering is eliminated in principle. The simulation shows that the proposed method has good matching performance, which is suitable for autonomous underwater vehicle navigation.